IN VITRO ANTIMICROBIAL ACTIVITY AND MOLECULAR CHARACTERIZATION OF BACILLUS AMYLOLIQUEFACIENS ISOLATED FROM SIMILIPAL BIOSPHERE RESERVE, ODISHA, INDIA - DAS, IPSITA; KU PANDA, MRUNMAYA; C.RATH, CHANDI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of our study was to isolate and identify the bacteriocinogenic strain exhibiting broad range antimicrobial activity and to analyze the effect of different culturing conditions on the production of an antimicrobial metabolites isolated from the soil of Simlipal Biosphere Reserve, India. Methods: In the current study, bacterial strains were screened for antimicrobial activity from soil samples of five different regions. The effect of varying culture conditions such as pH, incubation period, and temperature along with carbon and nitrogen sources with and without certain salts was studied. The characterization of the potent strain was studied by morphological, biochemical, and 16S rRNA genetic sequencing. A phylogenetic affiliation of the strain was studied. Results: A total of 31 out of 245 strains isolated from soil were screened on the basis of antimicrobial results against the test pathogens. On the basis of bacteriocin-like inhibition studies method, one potential isolate that exhibited the highest inhibition against all the pathogens was selected. The optimization of highest antimicrobial metabolite production by the isolate with the influence of physical parameters was found as the incubation period of 3 days with 37°C temperature at pH 8 and for the chemical parameters dextrose was showed the most effective carbon sources when implemented with salts and yeast extract as the best sources of nitrogen with salts. The crude metabolite showed an absorbance peak value of 1.234 with optimum ƛ-max at 214 nm. The potent isolate showed maximum identity with Bacillus amyloliquefaciens (99% similarity) with highest query coverage on basic local alignment search tool search analysis of the 16S rDNA sequence. Phylogenetic analysis revealed close affiliation of the isolate with B. amyloliquefaciens (KC494392.1) having antimicrobial activity. Conclusion: The findings revealed that the incubation period, temperature, pH, and the culture medium have a direct influence on the production of metabolites. These parameters can be modified for the improvement of the fermentation process.